2020
DOI: 10.31729/jnma.5284
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, behavior, perception and practices of Nepalese during lockdown due to COVID-19 pandemic

Abstract: Introduction: COVID-19 infection is caused by a new strain of SARS CoV-2 virus, which transmits directly from person-to-person and has become a pandemic. To counteract this, actions related to mass quarantines or stay-at-home orders have been used termed as lockdown. This study aims to study lifestyle, behaviour, perception and practice of people regarding during the lockdown. Methods: An online survey was conducted with structured questionnaire in Google forms after ethical approval from Nepal Health Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Similar to many other countries, Nepal has massively endured unprecedented COVID pandemic with huge economic loss ( 24 ). To stop the rapid spread of SARS-CoV-2, the GoN has taken actions such as stay-at-home and mass quarantines ( 25 ). Movement restriction of people appears the most efficient non-clinical intervention to contain the spread of COVID, especially in resource-limited nations such as Nepal.…”
Section: The Government Of Nepal's Response To the Covid-19 Pandemicmentioning
confidence: 99%
“…Similar to many other countries, Nepal has massively endured unprecedented COVID pandemic with huge economic loss ( 24 ). To stop the rapid spread of SARS-CoV-2, the GoN has taken actions such as stay-at-home and mass quarantines ( 25 ). Movement restriction of people appears the most efficient non-clinical intervention to contain the spread of COVID, especially in resource-limited nations such as Nepal.…”
Section: The Government Of Nepal's Response To the Covid-19 Pandemicmentioning
confidence: 99%
“…The study was based on the descriptive design from quantitative approach. An online survey using a cross-sectional design and convenient sampling was conducted (Kandel, Lamsal, Yadav, Bhandari, Adhikari, & Poudel, 2020). Data was collected by sending survey questionnaire via Microsoft teams and messenger.…”
Section: Methodsmentioning
confidence: 99%
“…[12] The Nepali version of the WHOQOL-BREF was used to assess QOL in this study. [13] Nepali version of the WHOQOL-BREF was used in Nepal as well [14] It is a 26 items self-rating questionnaire, giving scores to overall QOL (item 1, 2) and its four dimensions: physical health (e.g., sleep quality, energy and tiredness) (item 3,10,16,15,17,4,18) , psychological health (e.g., positive emotion, self-esteem, personal beliefs) (item 5,7,19,11,26,6), social relationships (e.g., social support and sexual activity) (item 20,22,21), and environmental health (e.g., climate, transportation, and healthcare assistance) (Item 8, 23, 12, 24, 13, 14, 9, 25). Items ask participants to rate their QOL during the last two weeks and each of them are rated on a 5-point Likert scale.…”
Section: Section 2: Health Related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…[6] In Nepal, majority 404 (72.8%) of Nepalese people were stressed and majority of the respondents 353 (63.6%) were adversely affected by professional works or suffered economic loss in business or lost their job during lockdown period in pandemic. [7] A qualitative study done among the public in Kathmandu, Kanchanpur, Bajura and Jhapa districts of Nepal revealed that many people shared the experiences of anxiety, fear of being infected, and stress due to lack of interaction during first wave of COVID-19 Pandemic. [8] The economic recessions in Nepal due to this pandemic have put significant financial pressure on many families which can effect overall health related quality of life.…”
Section: Introductionmentioning
confidence: 99%